The challenges of maintaining indigenous ecological knowledge - McCarter, Joe, author; Gavin, Michael C., author; Baereleo, Sue, author; Love, Mark, author; Resilience Alliance, publisher (Colorado State University. Libraries, 2014)
Increased interest in indigenous ecological knowledge (IEK) has led to concern that it is vulnerable amidst social and ecological change. In response, multiple authors have recommended the establishment of programs for the maintenance and revitalization of IEK systems. However, few studies have analyzed the methods, opportunities, and challenges of these programs. This is a critical gap, as IEK maintenance is challenging and will require layered and evidence-based solutions. We seek to build a foundation for future approaches to IEK maintenance. First, we present a systematic literature review of IEK maintenance programs (n = 39) and discuss the opportunities and challenges inherent in five broad groups of published approaches. Second, we use two case studies from the Republic of Vanuatu to illustrate these challenges in more depth. The first case study takes a community-based approach, which has inherent strengths (e.g., localized organization). It has, however, faced practical (e.g., funding) and epistemological (changing modes of knowledge transmission) challenges. The second case study seeks to facilitate IEK transmission within the formal school system. Although this model has potential, it has faced significant challenges (e.g., lack of institutional linkages). We conclude that supporting and strengthening IEK is important but that serious attention is needed to account for the social, situated, and dynamic nature of IEK. In closing, we use the review and case studies to propose four principles that may guide adaptive and flexible approaches for the future maintenance of IEK systems.
Keywords: cultural revitalization; indigenous ecological knowledge; Malekula; traditional ecological knowledge; Vanuatu